Simulações Climáticas Regionais na Amazônia durante a estação chuvosa, usando RegCM3 - CORRÊA, Irene Cristina Pe (2019)
The present paper presents a contribution on the climate modelling studies with emphasis on seasonal rainfall variability over the Amazon basin, during the austral summer (DJF) and autumn (MAM) rainy seasons. Based on ITCP RegCM3 climate simulations for a 12- yr period (1998/99 to 2008/09) using high resolution domain scale (40 km) and two different convection schemes (Grell and MIT-Emanuel), it was investigated the model performance to simulate the regional pluviometric distribution with reference to the GPCP-, TRMM- and GAUGE-based rainfall data. The quantitative evaluation analysis showed that RegCM3 presents systematic errors, especially those related to the substantial dry bias in northeastern Amazon using Grell scheme and also abundant wet bias in southern Amazon using MIT convective scheme. Most importantly, it was found that the RegCM3 simulations using Grell scheme does not adequately reproduce ITCZ-related rainfall characteristics over the equatorial Atlantic Ocean. This is probably due the intensification of the tropospheric circulation located at eastern side of equatorial Atlantic Ocean. Although the MIT scheme produces systematically higher-than-observed rainfall over the Amazon and ITCZ regions, the spatial rainfall distributions and interannual variations showed closer correspondence with GPCP, TRMM and GAUGE data and much better than the Grell results.